The Occurrence of Three Allexiviruses from Imported Garlic in Indonesia - Nurdevi, Amanda Febriyanti; Nurulita, Sari; Diana, Didiet Rahayu; Hidayat, Sri Hendrastuti (HAYATI Journal of Biosciences, 2026)
International trade in fresh horticultural commodities poses a high risk of emerging pests and diseases, including plant viruses. Infections of potyvirus, carlavirus, and allexivirus cause mosaic disease on garlic and potential yield loss. Potyvirus and Carlavirus have been well studied in Indonesia, but not for Allexivirus. Therefore, this study aimed to detect and identify of allexivirus species from imported garlic (consumption garlic) using reverse-transcription polymerase chain reaction (RT-PCR). Samples of garlic bulbs were collected from the plant quarantine inspection site of the regional quarantine service, North Jakarta City, DKI Jakarta Province. Individual garlic cloves were then germinated in water media. Common symptoms observed include mosaic, yellow stripes, twisted leaves, and leaf malformation. Molecular detection was done by RT-PCR using specific primers for three allexivirus species, namely Garlic virus A (GarVA), Garlic virus B (GarVB), and Garlic virus E (GarVE). Specific DNA fragments for GarVA, GarVB, and GarVE were successfully amplified from all tested samples. Nucleotide sequence analysis using SDT Matrix revealed the highest similarity of GarVA, -B, and -E with Chinese garlic isolates, i.e., 99.5%, 99.1%, and 95.0%, respectively. Further analysis revealed that Indonesian allexiviruses demonstrated a high genetic diversity and have a close genetic relationship with isolates from China. This study provides information about the occurrence of three allexiviruses in Indonesia and suggests avoiding the use of imported garlic bulbs for vegetative propagation.